A survey of synchronization methods for parallel computers - Dinning, A. (Computer (Long Beach, Calif.), 1989)
An examination is given of how traditional synchronization methods influence the design of MIMD (multiple-instruction multiple-data-stream) multiprocessors. She provides an overview of MIMD multiprocessing and goes on to discuss semaphore-based implementations (Ultracomputers, Cedar, and the Sequent Balance/21000), monitor-based implementations (the HM/sup 2/p) and implementations based on message-passing (HEP, the BBN Butterfly and the Transputer).< >